2004
DOI: 10.1159/000077591
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Sevelamer in the Treatment of Uncontrolled Hyperphosphataemia of Haemodialysis Patients

Abstract: Background/Aim: The treatment of hyperphosphataemia is of major importance in the management of patients on dialysis. Traditional phosphate binders can be associated with undesirable effects. Recently, a new non-absorbable phosphate-binding polymer, sevelamer hydrochloride, has been available. Clinical information is scarce, and its cost could be a limiting factor for its wider use. No studies have evaluated its usefulness in uncontrolled hyperphosphataemic patients. Methods: We identified 34 patients with a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…There were more cases of adverse effects (meteorism, constipation, nausea, vomiting, etc.) related to sevelamer HCl (2250–3000 mg/day) than in reports from other countries (14,15) and the reason for the high incidence of these gastrointestinal problems is unclear. One possible reason is that Japanese people eat less dietary fiber compared with non‐Japanese (16,17), but whether this is true or not requires further investigation.…”
Section: Discussionmentioning
confidence: 88%
“…There were more cases of adverse effects (meteorism, constipation, nausea, vomiting, etc.) related to sevelamer HCl (2250–3000 mg/day) than in reports from other countries (14,15) and the reason for the high incidence of these gastrointestinal problems is unclear. One possible reason is that Japanese people eat less dietary fiber compared with non‐Japanese (16,17), but whether this is true or not requires further investigation.…”
Section: Discussionmentioning
confidence: 88%
“…Recently, sevelamer, which is a much‐awaited, non‐calcium, nonaluminum P binder, has become clinically available in Japan. Various clinical trials have shown that sevelamer, as well as the Ca‐containing P binders, had a beneficial effect on P management in dialysis patients (5–10). In Japanese clinical trials on sevelamer treatment, it was demonstrated that the compound could improve bone mineral derangement in ESKD (11).…”
Section: Phosphate Binders In Japanmentioning
confidence: 99%
“…Recently, a novel, non‐calcium phosphorus (P) binder, sevelamer hydrochloride (sevelamer), has become available in Japan. Sevelamer has been reported to be effective in P management and on reduced Ca load in dialysis patients in European countries and the United States (5–11). Sevelamer might bring about an alternative therapeutic strategy for bone and mineral disarrangement of CKD, which is reflected in the Kidney Disease Outcomes Quality Initiatives (K/DOQI) Clinical Guidelines for Bone Metabolism and Disease in Chronic Kidney Disease (12).…”
mentioning
confidence: 99%
“…Almost all dropouts were due to gastrointestinal problems, such as the onset or exacerbation of constipation, abdominal bloating, nausea or abdominal pain. In this regard, Almirall et al (15) reported that 67% of patients treated with sevelamer developed gastrointestinal symptoms. It is possible that the high number of dropouts in our study was due to the use of 3.0 g/day of Pi binders in both groups, and/or failure to reduce the dose of these drugs.…”
Section: Discussionmentioning
confidence: 99%